Results of the engineering run of the Coherent Neutrino Nucleus Interaction Experiment (CONNIE). (29th July 2016) - Aguilar-Arevalo, A.; Bertou, X.; Bonifazi, C.; Butner, M.; Cancelo, G.; Vázquez, A. Castañeda; Vergara, B. Cervantes; Chavez, C.R.; Motta, H. Da; D'Olivo, J.C.; Anjos, J. Dos; Estrada, J.; et al.
Abstract: The CONNIE detector prototype is operating at a distance of 30 m from the core of a 3.8 GW th nuclear reactor with the goal of establishing Charge-Coupled Devices (CCD) as a new technology for the detection of coherent elastic neutrino-nucleus scattering. We report on the results of the engineering run with an active mass of 4 g of silicon. The CCD array is described, and the performance observed during the first year is discussed. A compact passive shield was deployed around the detector, producing an order of magnitude reduction in the background rate. The remaining background observed during the run was stable, and dominated by internal contamination in the detector packaging materials. The in-situ calibration of the detector using X-ray lines from fluorescence demonstrates good stability of the readout system. The event rates with the reactor ON and OFF are compared, and no excess is observed coming from nuclear fission at the power plant. The upper limit for the neutrino event rate is set two orders of magnitude above the expectations for the standard model. The results demonstrate the cryogenic CCD-based detector can be remotely operated at the reactor site with stable noise below 2 e − RMS and stable background rates. The success of the engineering test provides a clear path for the upgraded 100 g detector to be deployed during 2016.